2019
DOI: 10.1097/pra.0000000000000409
|View full text |Cite
|
Sign up to set email alerts
|

Hallucinogens and Their Therapeutic Use: A Literature Review

Abstract: All studies were considered for downgrade if they exhibited poor design, insufficient number of subjects (N < 10), or other methodological flaws. Studies not meeting the above criteria, including case reports and expert opinion papers, were excluded entirely. Adapted with permission from the The Oxford Levels of Evidence 2 developed by the Oxford Centre for Evidence-Based Medicine (https://www.cebm.net/index.aspx?o=5653) and from Ishii 2015. 30

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 29 publications
0
5
0
1
Order By: Relevance
“…Humans have used psychedelics (also known as serotonergic hallucinogens) for thousands of years. Nonetheless, scientists became interested in these substances only after Albert Hofmann discovered the psychoactive properties of lysergic acid diethylamide (LSD) in 1943 (Begola and Schillerstrom 2019). Although hallucinogens are derived from multiple structural families, they are known as powerful agents producing profound changes in consciousness, perception, and mood (Halberstadt 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Humans have used psychedelics (also known as serotonergic hallucinogens) for thousands of years. Nonetheless, scientists became interested in these substances only after Albert Hofmann discovered the psychoactive properties of lysergic acid diethylamide (LSD) in 1943 (Begola and Schillerstrom 2019). Although hallucinogens are derived from multiple structural families, they are known as powerful agents producing profound changes in consciousness, perception, and mood (Halberstadt 2015).…”
Section: Introductionmentioning
confidence: 99%
“…It is suggested that naturally-occurring psychedelics have therapeutic potential due to the formation of new neural connections and modulation of the monoamine neurotransmitter system ( Carhart-Harris et al, 2018 ; Erritzoe et al, 2018 ). Recent evidence suggests that psychedelics can benefit various clinical populations, with rapid and sustained advances in post-treatment outcomes documented for depression ( Griffths and Grob, 2010 ; Begola and Schillerstrom, 2019 ), anxiety ( Griffths and Grob, 2010 ), and addictions ( Bogenschutz et al, 2015 ; Bogenschutz and Johnson, 2016 ). Importantly, the current evidence verified in animal studies has shown that classical psychedelics are not associated with physical dependence, abuse or withdrawal and have a low level of toxicity ( Reiff et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, there has been a shift within psychiatry to identify novel agents that can withstand scientific scrutiny (Begola & Schillerstrom, 2019 ; Stein & Simon, 2021 ). This shift has been associated with a re-examination of psychedelic agents for PTSD, including 3,4-methylenedioxymethamphetamine (MDMA/‘ecstasy’), psilocybin (‘magic mushrooms’), and ketamine (‘Special-K’; Varker et al, 2021 ).…”
mentioning
confidence: 99%